Analisis Keragaan Jagung Manis Seleksi Lini Bersari Bebas Sebagai Alternatif Terhadap Seleksi Hibrida F1 - Saiful Hikam; Sri Wahyuni; Paul B. Timotiwu (Inovasi Pembangunan : Jurnal Kelitbangan, 2016)
Plant breeding is done to get a good genetic in order to adapt with environment. F1 hybrid varieties and pollinated/OP is the result of plant breeding, which F1 hybrids are considered superior to OP. This study aimed to get a line of open pollinated sweet corn (OP) equivalent in performance to hybrids corn (F1). Assembling the sweet corn line segregating and bi- color with yellow rounded proportions 9 : 3 wrinkled yellow : 3 round white : 1 wrinkled white and 3 round : 1 wrinkled, from the Self six lines of sweet corn. Calculating the amount of genetic diversity and broad -sense heritability for long-term plant breeding program . This study randomized Complete Block Design Group. The data obtained are tested by Barlett and Levene s to homogeneity between treatments. Furthermore, the data will be analyzed by analysis of variance to obtain KNT hopes to infer the genetic diversity (σ2g) , broad -sense heritability (h2BS) , and the coefficient of genetic diversity (KKG). Line performance ranking is done by testing HSD. Boxplot analysis performed on the data to compare with standard commercial corn. Segregation of color and form of seeds tested with Test Goodness of Fit using the chi –squared. These results indicate that the achievement of the objectives that the sweet corn line SE and SU quivalent in performance to F1 hybrids corn. Achieving the goal of producing sweet corn segregation ( sweet seed in the form of round seeds and bi colors) in a single cob of sweet corn on the 6th line of corn grown. Genetic diversity and heritability proved in character broke anther , leaf number ,the number of male flowers, weight of 100 grains, grain weight pertongkol and production per m2 so the selection for plant breeding can be done.